The Vowel System of Podhale Goralian - Rubach, Jerzy; Łuszczek, Tomasz (Research in Language, 2019)
This paper is a report on the phonological research done in the past two years investigating Podhale Goralian. The data are drawn from our informants in Dzianisz. The paper establishes the system of surface contrasts in Goralian and identifies instances of complementary distribution. It is claimed that the renowned Podhale Archaism is no longer represented by the vowel [i]. Rather, the vowel has retracted to the central vowel [ɨ]. The original [ɨ], on the other hand, has lowered and fronted and is now best regarded as tense [e]. These transitions of vowels pose challenges for a phonological analysis. A sample of such analysis (Final Tensing) is shown in the framework of Optimality Theory.